Genome-Wide Identification and Characterization of TCP Family Genes in Pak-Choi [Brassica campestris (syn. Brassica rapa) ssp. chinensis var. communis] - Huang, Feiyi; Shi, Churan; Zhang, Yuhang; Hou, Xilin (Frontiers in Plant Science, 2022)
The TEOSINTE BRANCHED1/CYCLOIDEA/PROLIFERATING CELL FACTOR (TCP) gene family, a kind of plant specific transcription factor, is essential for stress response, cell growth, and cell proliferation. However, the characterization of TCP family is still not clear in Pak-choi [Brassica campestris (syn. Brassica rapa) ssp. chinensis var. communis]. In this study, genome-wide analysis of TCP gene family was performed and 26 TCP genes were identified in Pak-choi. Phylogenetic analysis demonstrated that the 26 BcTCPs were divided into two classes: Class I and Class II. Class II was further classified into two subclasses, CIN and CYC/TB1. The qPCR results suggested that most BcTCPs respond to abiotic stresses. The expressions of BcTCP3, BcTCP12, BcTCP21, and BcTCP22 were significantly changed under ABA and cold treatment. BcTCP3 and BcTCP12 were also up-regulated under osmotic treatment. Subcellular localization showed that BcTCP3 and BcTCP21 were located in the nucleus. Our results will facilitate revealing the functions and regulatory mechanisms of BcTCPs.